Did you know that a lack of vitamin B12 can trigger neurological diseases? (Research, Society and Development, 2022)
Vitamin B12, cyanocobalamin or cobalamin is a B-complex vitamin, water-soluble and of bacterial origin, synthesized exclusively by microorganisms, and for this reason, it is found only in foods of animal origin. For the absorption of cobalamin in the digestive system, it is essential that the gastrointestinal tract is in perfect condition, and this micronutrient can be found in protein-based diets. Malabsorption of cobalamin from food is the main cause of vitamin deficiency in adults. The clinical presentation of B12 deficiency is insidious and includes hematologic manifestations, gastrointestinal manifestations, and neurologic manifestations. For the analysis of the problem, a systematic and ordered research was used based on electronic data. Therefore, in view of the importance of vitamin B12 and the consequences of its deficiency in the body, this qualitative literature review study aimed to synthesize knowledge about the relationship between neurological diseases and the lack of vitamin B12, addressing topics of an educational nature. aimed at raising awareness on the subject, preventing diseases and supporting the development of reparative treatments. After several thematic approaches related to the subject, this work obtained the need to clarify to the whole society the importance of cobalamin for the development and correct functioning of the organism, so that this subject does not become a serious public health problem in the future.